2015
DOI: 10.18083/lcappl.2015.4.56
|View full text |Cite
|
Sign up to set email alerts
|

Optical, Mesomorphic and Photoelectric Properties of the Mix-substituted Phthalocyanine Ligands and their Metal Complexes of the A3B Type

Abstract: Смешанной конденсацией 3,6-дигексадецилоксифталонитрила (компонент А) с 4,5-дихлор-или 3,4,5,6-тетрахлорфталонитрилом (компонент В)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…19 In our previous reports on the structure and physicochemical properties of asymmetric phthalocyanine derivatives of A 3 Btype, it was shown that the number of acceptor substituents (two or four chlorine atoms) introduced to the molecule significantly affects electronic absorption spectra (both in solutions and thin films), energy of boundary orbitals (HOMO/LUMO), values of the dipole moment, and mesomorphic properties of those compounds. 16,18 A difference in photoelectric properties of heterophase systems based on phthalocyanines of this type in combination with fullerene C 60 was also observed. 16 In the present work, we continued our ongoing research and comprehensively examined the floating layer structure formed by asymmetric 1,4,8,11,15,18-hexaoctyloxy-22,23,24,25-tetrachlorophthalocyanine 1.…”
mentioning
confidence: 85%
See 2 more Smart Citations
“…19 In our previous reports on the structure and physicochemical properties of asymmetric phthalocyanine derivatives of A 3 Btype, it was shown that the number of acceptor substituents (two or four chlorine atoms) introduced to the molecule significantly affects electronic absorption spectra (both in solutions and thin films), energy of boundary orbitals (HOMO/LUMO), values of the dipole moment, and mesomorphic properties of those compounds. 16,18 A difference in photoelectric properties of heterophase systems based on phthalocyanines of this type in combination with fullerene C 60 was also observed. 16 In the present work, we continued our ongoing research and comprehensively examined the floating layer structure formed by asymmetric 1,4,8,11,15,18-hexaoctyloxy-22,23,24,25-tetrachlorophthalocyanine 1.…”
mentioning
confidence: 85%
“…16,18 A difference in photoelectric properties of heterophase systems based on phthalocyanines of this type in combination with fullerene C 60 was also observed. 16 In the present work, we continued our ongoing research and comprehensively examined the floating layer structure formed by asymmetric 1,4,8,11,15,18-hexaoctyloxy-22,23,24,25-tetrachlorophthalocyanine 1.…”
mentioning
confidence: 85%
See 1 more Smart Citation
“…In this work, we continue investigations concerning synthesis of sulfo-and alkylsulfamoyl derivatives of aryloxy-substituted phthalocyanines [2][3]. We have previously shown that the presence of donor and acceptor substituents imparts the ability for non-mesogenic compounds to show thermotropic mesomorphism [4][5][6][7]. While the introduction of sulfo or alkylsulfamoyl fragments into para-position with respect to the oxygen atom of aryloxy group of mixsubstituted phthalocyanines does not affect the ability of these compounds to exhibit mesomorphism.…”
Section: Introductionmentioning
confidence: 99%